YouTube: estrutura e ciberaudiência - um novo paradigma televisivo - Frigeri, Alexandre Machado (2011)
This study involved an analysis of the YouTubevideo on demand provider as an influential means of communication within the context of the so-called New Media, which use technologies that stand out for their high-volume access, multidirectional broadcasting and number of users. The new media differ from traditional media structures in that they enable more interactivity among users, greater production and transformation capability, and the insertion and embedment of new information. They also offer time schedule flexibility and access to contents not available through traditional media. Unlike the traditional mass media, which are unidirectional and less interactive, the new media are based on a multiuser constructed paradigm, and their content is not controlled (guided), thus enabling the reconfiguration of information. Within this logic, YouTube is considered an emergent and important communication phenomenon, a new communication paradigm characterized by a new way of watching TV. Our quest is to understand the ways in which YouTube users interact and the impact of YouTube on the overall process of social communication. Our analysis includes an evaluation of statistical researches (quantitative) and of descriptive qualitative research. The basic issues or research problems answered in this work include users perceptions of YouTube, the process of symbolic representation that YouTube itself assumes, and users practices in accessing and validating information. Cyber spectators use this new medium as a source of information about cultural, professional, technological, scientific, religious and other subjects. This medium is characterized by its more widespread use among different age groups, thus modifying the initial notion that YouTubeis destined for the amusement of young people (although this possibility is not excluded). The way in which new media content is received differs from that of traditional TV, suggesting the creation of a new paradigm. This study addresses concepts of cyberculture, cultural studies, semiotics and communication based on the logic of the new media. An analysis is made of the contrast between the terms media and new media, the identitary issue, the configuration of a medium for relationships in cyberculture, and the process of semiotics of the senses and perceptions, as well as the original and pertinent findings of this descriptive qualitative research, part of which is unique and the result of a partnership with the IBOPE/NetRatings Group